2018
DOI: 10.3390/s18030730
|View full text |Cite
|
Sign up to set email alerts
|

Redox Cycling Realized in Paper-Based Biochemical Sensor for Selective Detection of Reversible Redox Molecules Without Micro/Nano Fabrication Process

Abstract: This paper describes a paper-based biochemical sensor that realizes redox cycling with close interelectrode distance. Two electrodes, the generator and collector electrodes, can detect steady-state oxidation and reduction currents when suitable potential is held at each electrode. The sensor has two gold plates on both sides of a piece of chromatography paper and defines the interelectrode distance by the thickness of the paper (180 μm) without any micro-fabrication processes. Our proposed sensor geometry has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Yamamoto et al recently reported redox cyling in a paper-based device. 33 Yet, the experiment was limited to only a pair of electrodes. In this work, a new PON detection platform is designed by coupling TPE arrays, consisting of up to 8 electrodes, into a flow-based ePAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al recently reported redox cyling in a paper-based device. 33 Yet, the experiment was limited to only a pair of electrodes. In this work, a new PON detection platform is designed by coupling TPE arrays, consisting of up to 8 electrodes, into a flow-based ePAD.…”
mentioning
confidence: 99%
“…IDAs are very rarely used as low cost-PON sensors as they are limited by expensive conventional fabrication techniques, such as photolithography and chemical vapor deposition. , A few studies have adapted IDAs into PADs via chemical deposition and gravure printing. , However, their use was limited to resistance-based measurements, with no redox-based electrochemistry performed. Yamamoto et al recently reported redox cyling in a paper-based device . Yet, the experiment was limited to only a pair of electrodes.…”
mentioning
confidence: 99%
“…3C [79,94]. This electrode assembling configuration is highly attractive for implementation with reversible redox markers as the distance between the two electrodes defined by the thickness of thin-layer paper could be sufficiently small for redox cycling [95].…”
Section: External Electrodesmentioning
confidence: 99%
“…[8] The redox cycling system is also a powerful strategy to enable discrimination of redox species with different reaction characteristics since currents from chemically irreversible redox reactions are not being amplified. [9,10] Various electrode configurations and designs, both lateral and vertical approaches, have been reported and achieved very good signal amplification efficiencies. [11] Interdigitated electrodes (IDEs) in an array format are one of the most popular configurations due to their simplicity in terms of design and manufacturing.…”
Section: Introductionmentioning
confidence: 99%